PENGARUH IKLIM BELAJAR TERHADAP HASIL BELAJAR SISWA PADA PEMBELAJARAN IPS KELAS VIII DI SMP NEGERI 21 PONTIANAK - Suprayitno, Eko; Aminuyati, Aminuyati; Khosmas, F.Y (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis thesis entitled â€œThe effect of learning climate on student learning outcomes on social learning in eighth grade student of SMP Negeri 21 Pontianak.â€ This research aimed to know the effect of learning climate on student learning outcomes on social learning in eighth grade student of SMP Negeri 21 Pontianak. The method that used on this research was descriptive method. The collective data technique was done by the observation and indirect communication. The tool of data collection that used is observation chectlist, and questionnaire. Based on the research result, the learning climate of social learning in eighth grade student of SMP Negeri 21 Pontianak was in a controlled and good conditon. The student learning outcomes that took from the average of fourth times daily examination in the first semester, showed that the average of student result just reach 58,30 scored it means that many student didnâ€™t pass the minimum standard criteria achievement that setted by SMP Negeri 21 Pontianak whereas 75. It showed that there is an effect of learning climate on student learning outcomes. The signifacance effect between independent variable (x), learning climate and dependent variable (y), student learning outcomes or determiner coefficient (R2) the score was 0,219 or 21,9 % while the rest was 0,781 or 78,1 that caused by another factors.Â Keywords: Learning Climate, Learning Result, Social Learning